2015
DOI: 10.1111/jvh.12379
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of telbivudine treatment: an open‐label, prospective study in pregnant women for the prevention of perinatal transmission of hepatitis B virus infection

Abstract: We evaluated the efficacy and safety of telbivudine (LdT, 600 mg/day) vs control patients (no treatment) in decreasing vertical transmission of HBV, in HBeAg-positive mothers (HBVDNA >6log(10) copies/mL). HBeAg-positive pregnant women either in the second or third trimester were recruited in a prospective, case-control, open-label study, at the Second Affiliated Hospital of the Southeast University, China (February 2008-December 2010). Efficacy (month 7: HBVDNA (+), HBsAg (+) infants) in either the overall gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 20 publications
1
37
1
2
Order By: Relevance
“…Of the 32 RCTs that enrolled 4189 pregnant women, 17 studies evaluated the effect of LAM, 15 studies evaluated LdT, 3 studies evaluated TDF, and 3 studies evaluated both LAM and LdT . Of the 27 non‐RCT studies enrolling 5039 pregnant women, 10 evaluated LAM, 18 evaluated LdT, 3 studies evaluated TDF, 2 evaluated both LAM and LdT, and another 2 studies evaluated both LAM and TDF . The characteristics of pregnant women and newborns in the 59 studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 32 RCTs that enrolled 4189 pregnant women, 17 studies evaluated the effect of LAM, 15 studies evaluated LdT, 3 studies evaluated TDF, and 3 studies evaluated both LAM and LdT . Of the 27 non‐RCT studies enrolling 5039 pregnant women, 10 evaluated LAM, 18 evaluated LdT, 3 studies evaluated TDF, 2 evaluated both LAM and LdT, and another 2 studies evaluated both LAM and TDF . The characteristics of pregnant women and newborns in the 59 studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Although telbivudine (LdT) is the first drug to be assigned to Pregnancy Category B and it is generally considered safe for the treatment of CHB during pregnancy . In recent years, there have been reports of pregnant women treated with LdT during the third trimester of pregnancy to block mother‐to‐infant transmission (MTIT) of HBV ; however, there are very few reports about the safety of LdT treatment for the whole pregnancy. The present study aims to evaluate the safety of LdT treatment for chronic HBV infection during the whole pregnancy, to provide a reference for chronic HBV‐infected fertile women on how to block MTIT of HBV.…”
Section: Introductionmentioning
confidence: 99%
“…Although practice guidelines do not recommend the use of telbivudine as a first‐line agent for the treatment of CHB, the European Association for the Study of the Liver and the Asian‐Pacific Association for the Study of the Liver guidelines recommend telbivudine as one of the two preferred drugs to be used for the prevention of perinatal and intrauterine HBV transmission in the last trimester of pregnancy in HBsAg‐positive women with high levels of viremia (serum HBV DNA > 10 6‐7 IU/mL) . Several studies showed that maternal treatment with telbivudine when compared with no treatment or placebo during the third trimester of pregnancy was effective in reducing vertical transmission of HBV infection . A meta‐analysis of seven clinical trials involving 644 pregnant women demonstrated that telbivudine use during late pregnancy was effective in interrupting mother‐to‐child transmission in newborns .…”
Section: Safety Profile Of Telbivudinementioning
confidence: 99%